Analyzing the citation impact of predatory journals in the health sciences. - Watson, Erin; Zhang, Li (Journal of the Medical Library Association, 2025)
Objective: Predatory journal articles do not undergo rigorous peer review and so their quality is potentially lower. Citing them disseminates the unreliable data they may contain and may undermine the integrity of science. Using citation analysis techniques, this study investigates the influence of predatory journals in the health sciences. Methods: The twenty-six journals in the "Medical Sciences" category of a known predatory publisher were selected. The number of articles published by these journals was recorded based on the information from their websites. The "Cited References" search function in Web of Science was used to retrieve citation data for these journals. Results: Of the 3,671 articles published in these predatory journals, 1,151 (31.4%) were cited at least once by 3,613 articles indexed in Web of Science. The number of articles that cited articles published in predatory journals increased significantly from 64 in 2014 to 665 in 2022, an increase of 10-fold in nine years. The citing articles were published by researchers from all over the world (from high-, middle-, and lower-income countries) and in the journals of traditional and open access publishers. Forty-three percent (1,560/3,613) of the citing articles were supported by research funds. Conclusions: The content from articles published in predatory journals has infiltrated reputable health sciences journals to a substantial extent. It is crucial to develop strategies to prevent citing such articles.